Terrorism, Radicalisation and Moral Panics: Media and Academic Analysis and Reporting of 2016 and 2017 'Terrorism'. (2nd November 2017) - Dingley, James; Herman, Sean
Abstract: Radicalism or radicalisation has become a serious political and academic theme in recent years and any incident involving Muslims now almost automatically acquires the cachet, as events in 2016 and 2017 have shown. However, despite vast sums and resources expended on the subject no one can define what they mean by 'it'. This should make us pause and question what precisely it is that causes so much alarm and is it worth the resources, time and effort employed to respond to it?